2022
DOI: 10.1142/s0218348x2240151x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Newly Developed Fractal-Fractional Model of Casson Fluid With Exponential Memory

Abstract: In the current research community, certain new fractional derivative ideas have been successfully applied to examine several sorts of mathematical models. The fractal fractional derivative is a novel concept that has been proposed in recent years. In the presence of heat generation, however, it is not employed for the free convection Couttee flow of the Casson fluid model. The core interest of the present analysis is to examine the Casson fluid under the influence of heat generation and magnetic field. The flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The nonlocality property of fractional derivatives is useful in predicting certain materials' memory and heredity properties in certain circumstances. As a result, the fractional derivative 34 37 can be defined physically as a memory search. Scholars from virtually all fields of science, technology, and engineering have been studying non-local operators of differentiation over the past few decades since they have the capability to incorporate more complex phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlocality property of fractional derivatives is useful in predicting certain materials' memory and heredity properties in certain circumstances. As a result, the fractional derivative 34 37 can be defined physically as a memory search. Scholars from virtually all fields of science, technology, and engineering have been studying non-local operators of differentiation over the past few decades since they have the capability to incorporate more complex phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…In [3], Abro et al utilized the fractal-fractional theory to discussed chaos in thermal convection of the fluid. Murtaza et al [4] investigated the thermal convection of Casson fluid flow in a micro channel by using the theory of FFD. The authors concluded that, fractal dimension provide larger memory effects than the usual fractional derivative.…”
Section: Introductionmentioning
confidence: 99%
“…Murtaza et al. [4] investigated the thermal convection of Casson fluid flow in a micro channel by using the theory of FFD. The authors concluded that, fractal dimension provide larger memory effects than the usual fractional derivative.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies [11][12][13] are referred to for better understanding of the ows mentioned above. Nanouids have more practical features [14][15][16] in uid mechanics due to technological advancements since the thermal properties of the nanouid are better (see for instance ref. 17) than those of the uids.…”
Section: Introductionmentioning
confidence: 99%